THE BANK’S TRANSITION TO THE DIGITAL ECONOMY TODAY - Xasanov Abdushohid; Muhammadiminova Nigora (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In this article, the digital economy is rapidly reshaping industries around the world, and the banking sector is no exception. In today's interconnected world, technology plays a critical role in the delivery, consumption and management of financial services.